The way it was - Khan, Z. A. (Zahir Alam). (Karachi : Ikram ul-Majeed Sehgal, 1998)
An ex-army officer's account of the history of Pakistan army.
Includes index.
Keywords: Khan, Z. A; Pakistan. -- Army -- History; Pakistan -- History, Military